Organic Molecular Tracers in PM2.5 at Urban Sites during Spring and Summer in Japan: Impact of Secondary Organic Aerosols on Water-Soluble Organic Carbon - Fumikazu Ikemori; Rie Nishimura; Shinji Saito; Masayuki Akiyama; Shigekazu Yamamoto; Akihiro Iijima; Seiji Sugata (Atmosphere, 2021)
To understand the characteristics of secondary organic aerosols (SOAs) and estimate their impact on water-soluble organic carbon (WSOC) in urban areas in Japan, we measured 17 organic tracers using gas chromatography–mass spectrometry from particulate matter with an aerodynamic diameter smaller than 2.5 μm collected at five urban sites in Japan during spring and summer. Most anthropogenic, monoterpene-derived, and isoprene-derived SOA tracers showed meaningful correlations with potential ozone in both these seasons. These results indicate that oxidants play an important role in SOAs produced during both seasons in urban cities in Japan. WSOC was significantly affected by anthropogenic and monoterpene-derived SOAs during spring and three SOA groups during summer at most of the sites sampled. The total estimated secondary organic carbons (SOCs), including mono-aromatic, di-aromatic, monoterpene-derived, and isoprene-derived SOCs, could explain the WSOC fractions of 39–63% in spring and 46–54% in summer at each site. Notably, monoterpene-derived and mono-aromatic SOCs accounted for most of the total estimated SOCs in both spring (85–93%) and summer (75–82%) at each site. These results indicate that SOAs significantly impact WSOC concentrations during both these seasons at urban sites in Japan.